Bound Flavin Model Suggests Similar Electron‐Transfer Mechanisms in Shewanella and Geobacter. Issue 11 (12th August 2014) - Okamoto, Akihiro; Nakamura, Ryuhei; Nealson, Kenneth H.; Hashimoto, Kazuhito
Abstract Certain microbes are capable of transporting electrons from the cell interior‐respiratory electron chain to insoluble electron acceptors located outside of the cell, a process referred to as extracellular electron transport (EET). Bacteria capable of EET are currently utilized as "living anode catalysts" in microbial fuel cells. Several EET mechanisms have been proposed, yet they lack molecular‐level consistency. Here, we review our recent work, presenting a "bound‐flavin cofactor" model, which we believe provides a suitable explanation for all of the published data to date for the model EET microbes of Shewanella oneidensis and Geobacter sulfurreducens. We discuss the interaction between free flavin and outer‐membrane c‐type cytochromes based on a protein–ligand binding model, the accumulation of cell‐secreted flavins in nanostructured electrodes, and EET through intermittent direct contacts or conductive extracellular appendages.